LEONAS JOVAIŠA’S THEORY OF PERSONALI TY: COMPA RATIV E ANALYSIS - Paulauskas, Rolandas (Acta Paedagogica Vilnensia, 2010)
The article is dedicated to L. Jovaiša’s significant contributions to the development and enhancement of psychological and educational sciences in Lithuania.In spite of the lengthy and ongoing debate about the teleology of human behavior, L. Jovaiša suggests that our activity motives are mostly determined by personal purposes and goals rather than external factors. Professor L. Jovaiša does not agree with the psychoanalytic opinion that unconscious drives such as libido and aggression serve as underlying forces of our conduct. He also debates the behavioristic approach regarding the influence of prior stimuli and operant conditioning that may determine human behavior. Although his optimistic approach to the quality of human nature, the dynamics of human needs and development of personality is somewhat similar to those of Gordon Allport and humanistic psychologists, L. Jovaiša argues that none of the current theories include temperamental, charactero logical, motivational, cognitive and other components of a live person. Personality structure is very complex and indivisible. Cognition cannot be separated from motivation, temperament, emotions, character, etc. L. Jovaiša’s personality theory is also educationally oriented as compared to other personality concepts. It has been empirically tested by his graduate students and other researchers and deserves a wider acknowledgement by European scholars. To this day the theory remains very unique and will continue to serve as the background for further research and educational purposes.
Keywords: Personality; personality structure; activity; motivation; traits